2016
DOI: 10.22630/pefim.2016.15.64.15
|View full text |Cite
|
Sign up to set email alerts
|

City Placement – Innovational Means of Promoting Cities

Abstract: A detail attempt of the “city placement” strategy, has been made in the article. Its main threads, components and decision making problems of the film producers teams have been emphasized. The author based his knowledge, in this case, on the diagnosis and analysis of the processes and decision making procedures adequate for big, Polish cities, their administrative authorities, promotional strategies and the rules of cooperation with media partners. Assumedly, the used process-structural conceptualizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Therefore, consumers in those countries usually have a weaker preference for local products and a stronger preference for foreign ones (Witkowski, 1998;Falkowski et al, 1996). Studies conducted in Poland showed a high level of consumer ethnocentrism among Polish consumers, especially in older, less educated buyers and this was slightly stronger among women (Good & Huddleston, 1995;Falkowski et al, 1996;Szromnik & Wolanin -Jarosz, 2013). Jin et al (2015) claimed that cosmopolitanism plays a role in predicting consumer ethnocentrism in developed countries but exerts no role in developing countries.…”
Section: Consumer Ethnocentrism and Cetscalementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, consumers in those countries usually have a weaker preference for local products and a stronger preference for foreign ones (Witkowski, 1998;Falkowski et al, 1996). Studies conducted in Poland showed a high level of consumer ethnocentrism among Polish consumers, especially in older, less educated buyers and this was slightly stronger among women (Good & Huddleston, 1995;Falkowski et al, 1996;Szromnik & Wolanin -Jarosz, 2013). Jin et al (2015) claimed that cosmopolitanism plays a role in predicting consumer ethnocentrism in developed countries but exerts no role in developing countries.…”
Section: Consumer Ethnocentrism and Cetscalementioning
confidence: 99%
“…For example, some studies demonstrated that consumer ethnocentrism is positively correlated with age, where older consumers are more ethnocentric (Witkowski, 1998;Shah & Ibrahim, 2012;Alsughayir, 2013;Lajevardi et al, 2014), and negatively with education and financial standing, where educated consumers and those more well -off are less ethnocentric (Bawa, 2004;Nadiri & Tümer, 2010). Some studies also found that women tend to be more ethnocentric consumers (Ferrin et al, 2012;Szromnik & Wolanin -Jarosz, 2013). However, the relationship with demographic variables is not always confirmed and consistent (Nadiri & Tümer, 2010).…”
Section: Consumer Ethnocentrism and Cetscalementioning
confidence: 99%
“…Today, the region, in Poland identified with the province, has become an active participant in the market game with specific resources, potential and capital of the place. It is the primary place for satisfying the broadly understood needs of both internal and external stakeholders often on the basis of the principle of proximity (Szromnik, 2016).…”
Section: Introductionmentioning
confidence: 99%